EFFECT OF DROTAVERINE, A PHOSPHODIESTERASE 4 INHIBITOR IN SCOPOLAMINE-INDUCED COGNITIVE IMPAIRMENT IN RATS - MK, KAYALVIZHI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Cognitive impairment (CI) is a progressive neurodegenerative disorder and causes significant dementia in the elderly. Intracellular cyclic AMP (cAMP) signaling has been well established in the mediation of memory. Phosphodiesterases (PDEs) are enzymes that catalyze the hydrolysis of cAMP and/or cyclic GMP. Drotaverine is a novel non-anticholinergic smooth muscle antispasmodic which acts by inhibiting PDE-4. It is now clinically used in smooth muscle spasms (intestinal, biliary and renal colic, irritable bowel syndrome, uterine spasms, etc.) without anticholinergic side effects. Since Drotaverine has PDE4 inhibition property, its role in learning and memory was evaluated in this study and found that it has memory enhancing effect comparable with donepezil in scopolamine-induced CI in rats. Methods: Learning and memory were assessed with two behavioral models, namely, elevated plus maze (EPM) and Y maze. CI was produced by scopolamine. Rats were divided into five groups, Group I treated with normal saline, Group II treated with scopolamine, and Groups III, IV, and V were treated with donepezil, Drotaverine, and both, respectively. Results: The result analysis revealed significant differences in transfer latency in EPM performance between Groups III, IV, V and Group II (***p<0.001). The results of spontaneous alternation in Y maze show that there was a significant difference among all the treatments groups (p<0.001). Conclusion: Drotaverine has promising memory enhancing effect in CI induced by scopolamine in rats. Further clinical trials are needed to prove this finding which has been elicited in animal models.